Comparison of the effect of marine-derived omega-3 fatty acids (n-3 FAs) as an adjunct to a non-steroidal inflammatory drug (NSAID) therapy vs NSAID therapy alone, for dogs with osteoarthritis - Wong, Lok Yee Stephanie; Govendir, Merran (Veterinary Evidence, 2022)
PICO question Does treatment with a non-steroidal anti-inflammatory drug (NSAID) with supplementation of marine-derived omega-3 fatty acids (n-3FAs) compared to the NSAID alone, result in an increased ability to exert force by the osteoarthritic limb(s) of dogs or alleviate other measures of osteoarthritis? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Two prospective, block-randomised, clinical trials Strength of evidence None Outcomes reported Kwananocha et al. (2016) investigated administration of carprofen supplemented with marine-derived n-3 FAs, to carprofen alone, administered over 4 weeks. Vijarnsorn et al. (2019) investigated administration of firocoxib supplemented with n-3FA, to firocoxib alone, for 4 weeks. There were no statistical differences between treatment groups at week 2 and week 4 post-treatment for either study. Both studies also reported orthopaedic assessment score (OAS) based on scoring the extent of patient lameness and pain in the affected joint. There were no statistical changes in OASs between treatment groups at week 2 or week 4 post-treatment for either study Conclusion There is no evidence that marine-derived n-3 FAs provide additional benefit when used as adjunctive agents with NSAIDs for the treatment of canine osteoarthritis How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.